Existence of solutions for a p-Laplacian Kirchhoff type problem with nonlinear term of superlinear and subcritical growth - IMANE, Melzi; TOUFIK, Moussaoui (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
This paper is concerned by the study of the existence of nonnegative and nonpositive solutions for a nonlocal quasilinear Kirchhoff problem by using the Mountain Pass lemma technique. Mathematics Subject Classification (2010): 35A15, 35B38, 35J62, 35J92.